Framing intervention in a multipolar world. Issue 3 (4th May 2019) - Cunliffe, Philip
ABSTRACT: In this contribution to the forum, I draw attention to the persistent inadequacy of existing categories in the field of international studies to capture and frame patterns of intervention today. It is to be expected that this inadequacy will become more and more apparent as the unipolar system of the post–Cold War era evolves into a multipolar system in which patterns of intervention will become more complex. I will show this by focusing on two aspects of contemporary intervention. First, I will argue that patterns of intervention today invert the classical predictions and expectations of International Relations theory with regard to the behaviour of emerging powers (resulting in what I call 'reverse revisionism' – i.e. revisionism by leading states). Second, I will argue that the categories applied to understand Western interventions, already problematic in themselves, cannot be stretched to cover the behaviour of non-Western and emerging states.